1989
DOI: 10.1007/bf00500923
|View full text |Cite
|
Sign up to set email alerts
|

Localization of bombesin-, neuropeptide Y-, enkephalin-and tyrosine hydroxylase-like immunoreactivities in rat coeliac-superior mesenteric ganglion

Abstract: The localization of bombesin- (BOMB) and enkephalin- (ENK) immunoreactive (IR) nerves was studied in rat coeliac-superior mesenteric ganglion complex in relation to neuropeptide Y (NPY)- and tyrosine hydroxylase (TH)-immunoreactive neurons with an immunofluorescence double-staining method. Very dense networks of BOMB-IR nerve terminals surrounded the majority of the principal ganglion cells, whether or not they were TH-IR. BOMB-IR nerves were specifically related to the non-NPY-IR neurons. Moderately dense net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…It is well known that the coeliac ganglion-mesenteric complex is also innervated by fibres of an adrenergic nature that come from other preaortic ganglia, and that it exhibits α and β adrenergic receptors [24,25]. The presence of such receptors in coeliac ganglion was demonstrated physiologically in adult rats [8,26].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the coeliac ganglion-mesenteric complex is also innervated by fibres of an adrenergic nature that come from other preaortic ganglia, and that it exhibits α and β adrenergic receptors [24,25]. The presence of such receptors in coeliac ganglion was demonstrated physiologically in adult rats [8,26].…”
Section: Discussionmentioning
confidence: 99%
“…Bars 250 nm Fig. 2b,c;Lindh et al 1988;Elfvin et al 1989;Gibbins et al 2003a), whereas in rats and mice, they are most easily recognised by their immunoreactivity to bombesin/gastrinreleasing peptide (Järvi 1989).…”
Section: Neuropeptides and Schwann Cellsmentioning
confidence: 96%
“…Prior to these studies, most of the information on the structure of enteric synapses came from ultrastructural analyses (e.g. see Gabella 1976Gabella , 1979Llewellyn-Smith et al 1981, 1989 showing that synapses within the enteric ganglia have a typical morphological appearance but that many boutons closely appose the somata of enteric neurons without obvious synaptic specialisations (Wilson et al 1981a,b;Li and Furness 2000). Subsequent ultrastructural immunohistochemistry has revealed that some types of enteric neurons form interconnected chains, within which most morphologically defined synapses are of a similar type (e.g.…”
Section: Enteric Ganglia -Complex Local Circuitsmentioning
confidence: 99%
“…The superior mesenteric ganglion is constituted by specific structures responding to the cholinergic stimulus such as the nicotinic and muscarinic receptors in the ganglionic neurons called principal neurons [5] and the muscarinic receptors present in the interneurons, such as the small intensely fluorescent (SIF) cells, and peptidergic cells [6]. Recent studies have shown that the superior mesenteric ganglion, through the ONP, participates not only in the regulation of the blood flow [7,8] but also in the ovary physiology [9].…”
Section: Introductionmentioning
confidence: 99%